CD83 expressed by macrophages is an important immune checkpoint molecule for the resolution of inflammation - Peckert-Maier, Katrin; Langguth, Pia; Strack, Astrid; Stich, Lena; Mühl-Zürbes, Petra; Kuhnt, Christine; Drassner, Christina; Zinser, Elisabeth; Wrage, Marius; Mattner, Jochen; Steinkasserer, Alexander; Royzman, Dmytro; et al. (Frontiers in Immunology, 2023)
Excessive macrophage (Mφ) activation results in chronic inflammatory responses or autoimmune diseases. Therefore, identification of novel immune checkpoints on Mφ, which contribute to resolution of inflammation, is crucial for the development of new therapeutic agents. Herein, we identify CD83 as a marker for IL-4 stimulated pro-resolving alternatively activated Mφ (AAM). Using a conditional KO mouse (cKO), we show that CD83 is important for the phenotype and function of pro-resolving Mφ. CD83-deletion in IL-4 stimulated Mφ results in decreased levels of inhibitory receptors, such as CD200R and MSR-1, which correlates with a reduced phagocytic capacity. In addition, CD83-deficient Mφ upon IL-4 stimulation, show an altered STAT-6 phosphorylation pattern, which is characterized by reduced pSTAT-6 levels and expression of the target gene Gata3. Concomitantly, functional studies in IL-4 stimulated CD83 KO Mφ reveal an increased production of pro-inflammatory mediators, such as TNF-α, IL-6, CXCL1 and G-CSF. Furthermore, we show that CD83-deficient Mφ have enhanced capacities to stimulate the proliferation of allo-reactive T cells, which was accompanied by reduced frequencies of Tregs. In addition, we show that CD83 on Mφ is important to limit the inflammatory phase using a full-thickness excision wound healing model, since inflammatory transcripts (e.g. Cxcl1, Il6) were increased, whilst resolving transcripts (e.g. Ym1, Cd200r, Msr-1) were decreased in wounds at day 3 after wound infliction, which strikingly reflects the CD83 resolving function on Mφ also in vivo. Consequently, this enhanced inflammatory response led to altered tissue reconstitution after wound infliction as shown by qPCR as well as histological analyses of wound areas on day 6. Thus, our data provide evidence that CD83 acts as a gatekeeper for the phenotype and function of pro-resolving Mφ.